2013
DOI: 10.5155/eurjchem.4.4.408-413.806
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanism of oxidation of amido black by sodium N-halo-p-toluenesulfonamides in acidic medium: Spectrophotometric approach

Abstract: KEYWORDSThe kinetics of oxidative decolorization of amido black (AB, Naphthol blue black) by chloramine-T (CAT) and bromamine-T (BAT) in acidic medium has been investigated spectrophotometrically (λmax = 618 nm) at 298 K. Kinetic runs were performed under pseudo first-order conditions of [Oxidant] . Stoichiometry of the reaction was found to be 1:4 and the oxidation products were identified. The reaction was studied at different temperatures and various activation parameters have been computed. Effects of p-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…A similar behaviour has been noted [5] in the oxidation of several other substrates using CAT and BAT. The facts furnished in the present research and the literature reports [33][34] led to conclude that BAT is a stronger oxidant compared to CAT.…”
Section: Relative Reactivity Of Cat and Batsupporting
confidence: 77%
See 2 more Smart Citations
“…A similar behaviour has been noted [5] in the oxidation of several other substrates using CAT and BAT. The facts furnished in the present research and the literature reports [33][34] led to conclude that BAT is a stronger oxidant compared to CAT.…”
Section: Relative Reactivity Of Cat and Batsupporting
confidence: 77%
“…Organic N-haloamines are sources of positive halogens and these reagents have been exploited as oxidant for a variety of substrates in both acidic and alkaline media [11][12][13]. Since organic N-haloamines have analogous chemical properties, it is predicted that identical equilibria exist in aqueous acidic and basic solutions of these compounds [18][19].…”
Section: Reactive Species Of Cat and Batmentioning
confidence: 99%
See 1 more Smart Citation
“…Scheme 71 Oxidation of levocarnitine by bromamine-T Shubha et al demonstrated the oxidative decolourisation of amido black (AB, Naphthol blue black) using an economically feasible, simpler and eco-friendly protocol (Scheme 72). 99 The kinetics of the oxidation of AB by chloramine-T (CAT) and bromamine-T (BAT) was spectrophotometrically (λmax = 618 nm) investigated in an acid medium at 298 K and the rate law was deduced as…”
Section: Synlett Accountmentioning
confidence: 99%
“…). 108 The reaction rate was found to exhibit a first-order dependence on both [oxidant]o, and [substrate]o, whereas a fractional-order dependence on the acid was recorded, leading to the rate law: rate = k[oxidant]o[BHCl][H + ] 0.52 . A rise in the reaction rate was encountered with a drop in the dielectric constant of the medium.…”
Section: Accepted Manuscriptmentioning
confidence: 99%